(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Oxidative stress has been assumed to contribute to the pathophysiology of schizophrenia. Increased oxidative stress is the result of either an increased production of free radicals or a depletion of the endogenous antioxidants. Objective: To assess the levels of oxidative stress and antioxidant status in schizophrenia. Materials and Methods: This observational study was carried out in the department of Pharmacology, Bangabandhu Sheikh Mujib Medical University from September 2013 to January 2015. Ninety three schizophrenia patients were enrolled as study group and 30 healthy indivuduals were taken as control group. The peripheral levels of several molecules associated with oxidative stress namely malondialdehyde (MDA), glutathione (GSH) and anti-oxidant status like plasma levels of ascorbic acid (vitamin C) and α-tocopherol (vitamin E) in 93 patients with schizophrenia and 30 healthy participants were assessed. Results: Study found that the schizophrenia group presented substantially higher levels of oxidative stress than the control group, as revealed by elevated quantities of the pro-oxidant MDA (6.3±0.5μmol/L in study group and 2.1±0.5μmol/L in control group), decreased levels of the antioxidants GSH (0.6±0.2mg/gm of Hb in study group and 2.1±0.5mg/gm of Hb in control group), plasma α-tocopherol and ascorbic acid. Results found were highly significant (p=0.001). Conclusion: In schizophrenia there are increased level of oxidative stress and decreased level of the antioxidants. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 40-43